The management of head-and-neck paragangliomas. - Capatina, C; Ntali, G; Karavitaki, N; Grossman, AB (2013)
Paragangliomas (PGLs) are tumours originating from neural crest-derived cells situated in the region of the autonomic nervous system ganglia. Head-and-neck PGLs (HNPGLs) originate from the sympathetic and parasympathetic paraganglia, most frequently from the carotid bodies and jugular, tympanic and vagal paraganglia, and are usually non-catecholamine secreting. Familial PGLs are considered to be rare, but recently genetic syndromes including multiple PGLs and/or phaeochromocytomas have been more thoroughly characterised. Nowadays, genetic screening for the genes frequently implicated in both familial and sporadic cases is routinely being recommended. HNPGLs are mostly benign, generally slow-growing tumours. Continuous growth leads to the involvement of adjacent neurovascular structures with increased morbidity rates and treatment-related complications. Optimal management mostly depends on tumour location, local involvement of neurovascular structures, estimated malignancy risk, patient age and general health. Surgery is the only treatment option offering the chance of cure but with significant morbidity rates, so a more conservative approach is usually considered, especially in the more difficult cases. Radiotherapy (fractionated or stereotactic radiosurgery) leads to tumour growth arrest and symptomatic improvement in the short term in many cases, but the long-term consequences are unclear. Early detection is essential in order to increase the chance of cure with a lower morbidity rate. The constant improvement in diagnostic imaging, surgical and radiation techniques has led to a safer management of these tumours, but there are still many therapeutic challenges, and no treatment algorithm has been agreed upon until now. The management of HNPGLs requires a multidisciplinary effort addressing the genetic, surgical, radiotherapeutic, oncological, neurological and endocrinological implications. Further progress in the understanding of their pathogenesis will lead to more effective screening and earlier diagnosis, both critical to successful treatment.